360° video: Interview with Dove Bradshaw, artist, New York, 12 September 2017 - Messham-Muir, Kit (StudioCrasher, 2017)
This is the second part of a two-part interview with New York-based artist, Dove Bradshaw. I very first interviewed Dove in 2012, right at the beginning of the StudioCrasher project, and I've interviewed her several times since. In 2015, I spent a few days with Dove in her studio while she created one of her 'Contingency' paintings. The process involved coating a canvas in silver, randomly throwing on its surface wooden sticks, and tracing their placement with a chemical that would mark the silver.